Syibhul ‘Iddah Bagi Suami Dalam Nalar Ulama - Subhan, Moh (ASASI: Journal of Islamic Family Law, 2023)
Iddah is the waiting period for a former wife who has been divorced by her former husband, whether through talaq, khulu, fasakh, or the death of her husband. During the iddah period, the former wife is prohibited from marrying another man. The development of the times, the increasingly progressive mindset and culture of society, will give rise to various new problems in both the social and legal fields. Laws that have been established for a long time but are considered to discriminate against certain communities should be re-examined. Because the situation and conditions have changed and the lifestyle has also changed, it is appropriate for legal rules to always be up to date and dynamic in order to be in line with the times. The emergence of the phenomenon of the idea of a waiting period for men (syibhul iddah) is proof that Islamic law is always responsive to the demands of the times. Although this issue has been discussed by the salaf scholars in fiqh books. But one thing that needs to be understood is that syibhul iddah has opened up a new space for reinterpretation of Islamic law in order to remain relevant to the progress of the times. The basic principle in reinterpreting Islamic teachings is the principle of justice and benefit for all parties.